2013
DOI: 10.4149/neo_2013_072
|View full text |Cite
|
Sign up to set email alerts
|

Clinical importance of myeloid antigen expression in Moroccan patients with adult B-lineage acute lymphoblastic leukemia.

Abstract: The prognostic significance of myeloid antigen (MyAg) expression in acute lymphoblastic leukemias (ALL), especially in adult patients, is still controversial. In the present report, frequency and clinical significance of MyAg (CD13 and/or CD33) in blast cells were assessed in 80 consecutive adult (≥18 years) patients with B-lineage acute lymphoblastic leukemia (B-ALL), representing 66.7% of 120 patients diagnosed as having ALL during the study period. Immunophenotyping was used to classify leukemic cells as Bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…All EDTA-anticoagulated PB/ BM samples were immediately transported to the Cytometery Laboratory of the National Hygiene Institute of Morocco for immunophenotyping. All the samples were evaluated by flow cytometry, using CD45 expression vs side scatter to analyze the blast cell population as described earlier [4]. T-lymphoid antigens included CD1a, CD3, CD4, CD5, CD7 and CD8; B-lymphoid antigens included CD10, CD19, CD22, and cytoplasmic CD79a.…”
Section: Methodsmentioning
confidence: 99%
“…All EDTA-anticoagulated PB/ BM samples were immediately transported to the Cytometery Laboratory of the National Hygiene Institute of Morocco for immunophenotyping. All the samples were evaluated by flow cytometry, using CD45 expression vs side scatter to analyze the blast cell population as described earlier [4]. T-lymphoid antigens included CD1a, CD3, CD4, CD5, CD7 and CD8; B-lymphoid antigens included CD10, CD19, CD22, and cytoplasmic CD79a.…”
Section: Methodsmentioning
confidence: 99%
“…In the past, it was believed that the prognosis of ALL showing expression of myeloid antigen (Mye(+)ALL) was poorer than that of ALL with no myeloid antigen expression (Mye(–)ALL). However, recent papers suggested that there was no significant difference ­between the prognosis of these 2 groups (22–23–25). As previously mentioned, our 3 cases were different from those described in other reports.…”
Section: Discussionmentioning
confidence: 97%